Towards a holistic ministry to the Kwe San communities in the Tsumkwe constituency in Namibia - Coetzee, Ernst (Stellenbosch : Stellenbosch University, 2008)
Thesis (M.Div. (Practical Theology and Missiology))--Stellenbosch University, 2007.